2006
DOI: 10.1128/jb.00438-06
|View full text |Cite
|
Sign up to set email alerts
|

Straight-Chain Fatty Acids Are Dispensable in the Myxobacterium Myxococcus xanthus for Vegetative Growth and Fruiting Body Formation

Abstract: Inactivation of the MXAN_0853 gene blocked the production in Myxococcus xanthus of straight-chain fatty acids which otherwise represent 30% of total fatty acids. Despite this drastic change in the fatty acid profile, no change in phenotype could be observed, which contrasts with previous interpretations of the role of straight-chain fatty acids in the organism's development.Myxobacteria have very complex fatty acid (FA) profiles, with up to 40 different compounds belonging to all known classes of FAs (2, 27). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Thirty-two were identified in Nannocystineae and 44 in Cystobacterineae. In Myxococcaceae alone, from the latter suborder, 34 were identified, approximately the same number as reported earlier (1,2,6). Most surprising was the discovery of 49 FAs in Sorangiineae.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Thirty-two were identified in Nannocystineae and 44 in Cystobacterineae. In Myxococcaceae alone, from the latter suborder, 34 were identified, approximately the same number as reported earlier (1,2,6). Most surprising was the discovery of 49 FAs in Sorangiineae.…”
Section: Resultssupporting
confidence: 69%
“…Certain species of Corallococcus and Myxococcus have been used as the preferred models in most FA biosynthesis (1,4,42) and developmental studies (2,13,26,41). In Pyxidicoccus, the FA composition was evaluated here for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…The bkd mutant showed a high excess of this and other SCFAs, which would result in an excess of the required signal and therefore in a loss of the chemotaxis. However, recent analysis of a mutant that produces only trace amounts of SCFAs revealed that this FA or the corresponding PE is not required for fruiting body formation or sporulation as both occurred indistinguishable to the wild type (25). Interestingly, inactivation of the bkd locus does not lead to a complete loss of iso-FA production, which is due to the presence of a novel alternative pathway to isovaleryl-CoA ( Fig.…”
Section: (16) From Stigmatella Aurantiaca)mentioning
confidence: 99%
“…25 Furthermore, myxobacteria produce a variety of different fatty acids with unknown biological function. However, Bode et al 26 have shown iso-branched fatty acids play a role in the myxobacterial life cycle. A decrease in iso-branched fatty acid production resulted in a strongly delayed and reduced aggregation and sporulation.…”
Section: A Rt Ic Le In F O Abstractmentioning
confidence: 99%